The COVID-19 Treatment Landscape: A South African Perspective on a Race Against Time - Hendricks, Candice Laverne; Herd, Candice; Nel, Marcel; Tintinger, Gregory; Pepper, Michael Sean (Frontiers in Medicine, 2021)
The pandemic caused by SARS-CoV-2 has infected more than 27 million people worldwide (as of 07 September 2020).(1) Severe disease is believed to be secondary to the cytokine release syndrome (CRS or “cytokine storm”) which causes local tissue damage as well as multi-organ dysfunction and thrombotic complications. Due to the high mortality rates in patients receiving invasive ventilation, practice has changed from “early-intubation” for acute respiratory distress syndrome (ARDS) to a trial of non-invasive ventilation (NIV) or high flow nasal cannula (HFNC) oxygen. Reports indicating the benefit of NIV and HFNC have been encouraging and have led to more than 20 000 such devices being manufactured and ready for roll-out in South Africa (SA) as of July 2020. The need to identify drugs with clear clinical benefits has led to an array of clinical trials, most of which are repurposing drugs for COVID-19. The treatment landscape reflects the need to target both the virus and the effects of the virus such as the CRS and thrombotic complications. Conflicting results have the potential to confuse the implementation of coordinated treatment strategies and guidelines. The purpose of this review is to address pertinent areas in the current literature on the available medical treatment options for COVID-19.